2004
DOI: 10.1111/j.1551-2916.2004.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stress To Produce Highly Oriented Tetragonal Lead Zirconate Titanate (PZT 40/60) Thin Films and Resulting Electrical Properties

Abstract: Thin films of Pb(Zr 0.4 Ti O.6 )O 3 produced by chemical solution deposition were used to study the effects of stress from different platinized single-crystal substrates on film orientation and resulting electrical properties. Films deposited on MgO preferred a (001) orientation due to compressive stress on the film during cooling through the Curie temperature (T C ). Films on Al 2 O 3 were under minimal stress at T C , resulting in a mixture of orientations. Those on Si preferred a (111) orientation due to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 42 publications
(44 reference statements)
1
36
1
Order By: Relevance
“…We note that experimentally PZT films on Si substrates contain polydomain microstructures that form so as to relax thermal stresses due to the TEC mismatch and the transformational stresses due to the FE-PE phase transformation at T C . [59][60][61][62][63][64][65][66] Several studies have been reported which provide a rigorous analysis of polydomain heterostructures in epitaxial FEs taking into account these (volumetric) sources of internal stresses as well as localized strain fields near defects using thermodynamic models and phase-field approaches. 20,55,67,68 Therefore, to describe the experimental observations, more sophisticated models need to be developed to describe the effect of grain and domain boundaries, grain texture, and the extrinsic contribution to the pyroelectric coefficient resulting from reversible domain wall motion.…”
Section: Resultsmentioning
confidence: 99%
“…We note that experimentally PZT films on Si substrates contain polydomain microstructures that form so as to relax thermal stresses due to the TEC mismatch and the transformational stresses due to the FE-PE phase transformation at T C . [59][60][61][62][63][64][65][66] Several studies have been reported which provide a rigorous analysis of polydomain heterostructures in epitaxial FEs taking into account these (volumetric) sources of internal stresses as well as localized strain fields near defects using thermodynamic models and phase-field approaches. 20,55,67,68 Therefore, to describe the experimental observations, more sophisticated models need to be developed to describe the effect of grain and domain boundaries, grain texture, and the extrinsic contribution to the pyroelectric coefficient resulting from reversible domain wall motion.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis was that the comparatively larger thermal expansion coefficient of Ni, relative to Si, and the small thickness of the foil substrate, would facilitate ferroelastic domain wall motion relative to films on Si. 13 Out-of-plane polarization in PZT films should yield large remanent polarizations and low dielectric permittivities as compared with PZT films on Si, which have a significant fraction of polarization which lies in-plane. 13 …”
mentioning
confidence: 98%
“…13 Out-of-plane polarization in PZT films should yield large remanent polarizations and low dielectric permittivities as compared with PZT films on Si, which have a significant fraction of polarization which lies in-plane. 13 …”
mentioning
confidence: 98%
“…22 Furthermore, reports indicate that the stress state upon cooling through the Curie temperature can affect the domain configuration, and thus dielectric properties, in tetragonal PZT thin films. 23 A tensile stress on cooling from the cubic state yields a preferred orientation of the c-axis in the plane of the substrate, whereas a compressive stress would form the c-direction normal to the substrate. The composition in the present study (i.e., 53/47) was on the rhombohedral/tetragonal phase boundary, and preferred orientation of domains could not be substantiated by XRD or SEM.…”
Section: Resultsmentioning
confidence: 99%